Digital Preaching Rhetoric on Tiktok Media: Case Study of Habib Husein Ja’far Account - Muhazzib, Naufal; Hapsari, Twediana Budi (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
This study analyzes the rhetorical strategies employed in digital da'wah through Habib Husein Ja'far's TikTok account, focusing on integrating Aristotle's rhetorical elements: Ēthos, Pathos, and Logos. Using a qualitative content analysis approach, the study examined ten selected TikTok videos uploaded between June and August 2024. The data were analyzed using a thematic coding framework that identified verbal, visual, and emotional cues corresponding to each rhetorical element. The findings reveal that Habib Husein Ja'far constructs ēthos through consistent use of culturally resonant fashion and informal yet authoritative speech. Pathos is activated through emotionally charged thumbnails, personal narratives, and audio-visual editing that appeals to viewers' feelings. Logos appears in simplified language, analogies, and occasional textual references to Islamic sources, enhancing message clarity and coherence. Notably, the most viral video, garnering over 10 million views, illustrates the effective convergence of these rhetorical elements in a short, relatable format. This study underscores the significance of rhetorical literacy in digital da'wah and demonstrates how TikTok can serve as a powerful platform for religious engagement. The results suggest that future da'wah practices can benefit from a balanced, theory-informed rhetorical approach that adapts to platform-specific audience dynamics while preserving the core values of Islamic communication.